Tanda-Tanda dalam Iklan Komersial di Televisi (Analisis Semiotika pada Iklan Susu Sgm Eksplor Presinutri 3) - Herawati, Erni; Rosidah, Rosidah (Humaniora, 2013)
Advertisement is one of promotional tools used by marketer to communicate with its audience or consumer which can be done through newspaper, magazine, internet, radio, and/or television. Using advertisement, the marketer tries to create signs in the message to the audience to make sure they really understand the message. The objective of the study is to analyze how the signs are created in the texts displayed on infant formula SGM Eksplor Presinutri 3 TV advertisement. The metodology is qualitative research using semiotics analysis. Peirce semiotics approach is applied to explore the signs in the advertisement. Secondary data were used, also supported by study literature, to conduct a deep analysis of this study. The research finding shows signs were used by the marketer to deliver the message of this product.